Influence of the compatibilizers on the physico-mechanical properties of the blend based on nitrile butadiene and chloroprene rubber. - Liên, Trần Kim; Hải, Lương Như; Trinh, Phạm Thế; Khải, Nguyễn Quang; Kháng, Đỗ Quang (Vietnam Journal of Chemistry, 2012)
In this paper, nitrile butadiene (NBR)/chloroprene (CR) blends added compatibilizers (made from Cashew nut shell liquid - DLH order tung oil-D01) were prepared for improving the mechanical properties, environmental resistance and the thermal stability of material. The characterization of the mechanical properties was performed according to the Vietnamese Standards. The thermal stability, the morphology of the materials depending on the blend composition were investigated by the thermal gravimetric analysis (TGA) and scanning electron microscopy (SEM). The results show that blend NBR/CR (50/50) added 1% compatibilizers (specially DLH) are better compatible, well-dispersed and compact structure are obtained. The mechanical properties, environmental resistance and the thermal stability of the materials were considerablely improved.